2007
DOI: 10.1016/j.cardiores.2007.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Right-ventricular failure is associated with increased mitochondrial complex II activity and production of reactive oxygen species

Abstract: These data show that the development of PAH-induced RV heart failure is associated with an increased capacity for ROS production by NADPH oxidase as well as mitochondria. The selective increase in expression and activity of mitochondrial Complex II may be particularly important for ventricular ROS production in heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
133
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 52 publications
14
133
0
1
Order By: Relevance
“…Interestingly, only complex I subunits were up-regulated during muscle differentiation ( Figure 7A). The discrepancy in expression levels of mETC complex subunits has been reported previously [37,38] and is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, only complex I subunits were up-regulated during muscle differentiation ( Figure 7A). The discrepancy in expression levels of mETC complex subunits has been reported previously [37,38] and is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Although there are conflicting data regarding the relative susceptibility of immature hearts to IR injury relative to mature hearts, our data demonstrate the key role of ROS in myocardial apoptosis and dysfunction in neonates. A similar role for ROS in IR injury has been reported in adults (31).…”
Section: Discussionsupporting
confidence: 80%
“…This was corroborated by a recent study (28) of PAH in rats in which we detected increased oxidative stress in cardiomyocytes of the failing RV. In this study, NADPH oxidase and mitochondria were identified as sources of the increase in ROS production.…”
supporting
confidence: 90%
“…In this study, NADPH oxidase and mitochondria were identified as sources of the increase in ROS production. These changes were specific to the overloaded RV, since they were not observed in the left ventricles (LVs) of the same hearts (28). The oxidative stress may at least in part account for the activation of proapoptotic pathways found in the failing RV in PAH (2) but may also account for other aspects of pathological remodeling.…”
mentioning
confidence: 99%